Pengaruh Financial Distress, Profitabilitas dan Company Growth Terhadap Konservatisme Akuntansi: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Sudradjat Sudradjat (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aims to determine the effect of financial distress, profitability, and company growth on accounting conservatism. The researcher uses secondary data, namely the financial statements of manufacturing companies in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange for the 2018-2020 period. In this study, there are 27 samples used in processing research data which were selected using the purposive sampling method. The data analysis method used in this study is the multiple linear regression analysis methods. The findings showed that (1) financial distress and company growth had a significant negative effect on accounting conservatism. (2) The profitability had a significant positive effect on accounting conservatism. (3) Simultaneously financial distress, profitability, and company growth had an effect on accounting conservatism.